Penyusunan Indeks Artikel Jurnal Beranotasi Bidang Teknologi Tahun 2010 - 2012 di Perpustakaan STMIK Indonesia Padang - Astuti, Tika; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this study is to describe the process of indexing journal annotated technology. Collection of annotated journal articles index technology done by observation and direct observation to collect data directly from the original source journals in library technology STMIK Indonesia Padang. Based on data analysis concluded, first, collecting journals done directly. Secondly, all journals that have been successfully traced and then grouped to be selected, the number of journals in the field of technology from 2010 -2012 there were six pieces journal article in which there are 70 titles. Fourth, collected from indexing keywords, author name, and journal title. fifth, the next step to do is typing an annotated index. Keywords: annotated index; indexing; articles index